EFFECT OF ANTIVIRAL THERAPY ON HEMATOLOGICAL PARAMETERS IN PATIENTS WITH CHRONIC HEPATITIS - Saeed, Shahzad; Khattak, Muhammad Irfan; Hussain, Tassawar (Pakistan Armed Forces Medical Journal, 2006)
Objective: To find out the effect of antiviral therapy on hematological parameters in patients of chronic hepatitis.Design: Interventional descriptive study.Place and Duration of Study: Military hospital (MH) Rawalpindi Pakistan from May to Oct 2004.Patients and Methods: 31 patients admitted to M.H Rawalpindi for treatment of chronic hepatitis were studied. Their hematological parameters including Total Leucocyte count (TLC), Haemoglobin (Hb) and Platelet count (Plt) were recorded before starting antiviral therapy and then at 3 monthly intervals. All the patients were given Inj Alpha-Interferon (INF) & Tab Ribavirin as antiviral therapy. Data was collected over a period of 6 months. Descriptive statistics were applied to the recorded data using SPSS ver-10.0 for analysis.Results: 31 patients with mean age + SD 38.58 + 8.85 years (range 16-49 years) were studied. There was mean hemoglobin (Hb) fall of 0.87g/dl at 3 months and 2g/dl at 6 months of antiviral therapy. Mean Total leukocyte count (TLC) fall of 1.30x109/L at 3 months and 1.87x109/L was noted at 6 months. Similar downward trend was noted in Platelet (Plt) values with mean fall of 23.19x109/mm3 and 28.29/ mm3 at 3 and 6 months of antiviral therapy respectively. 10% of the cases developed clinically significant anemia as evidenced by hemoglobin 11g/dl after 6 months of antiviral therapy. Clinically significant leucopenia (< 2.5x109/l) was noted in 7% of the cases. This fall was noted only in first three months of treatment.Conclusion: There is significant decrimental response of hematological parameters to antiviral therapy.